2014
DOI: 10.1016/s1995-7645(14)60241-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic and flavonoid contents and anti-oxidative potential of epicarp and mesocarp of Lagenaria siceraria fruit: a comparative study

Abstract: The findings of the study suggest that epicarp is a better source of antioxidants than the mesocarp, and the ethyl acetate fractions of both the parts contain higher contents of antioxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Likewise, the antioxidant capacity in the hydrophilic phase was superior to that obtained in the lipophilic phase (Table ). These results are similar to those previously reported by Usenik and others (), Ahmed and others (), and Solorzano‐Morán and others () where they demonstrated that the total antioxidant capacity of the epicarp was greater in comparison with the pulp for P. domestica L., L. siceraria , and S. purpurea fruits, respectively. In these studies, the antioxidant capacity of the hydrophilic and lipophilic phases was not determined separately.…”
Section: Resultssupporting
confidence: 92%
“…Likewise, the antioxidant capacity in the hydrophilic phase was superior to that obtained in the lipophilic phase (Table ). These results are similar to those previously reported by Usenik and others (), Ahmed and others (), and Solorzano‐Morán and others () where they demonstrated that the total antioxidant capacity of the epicarp was greater in comparison with the pulp for P. domestica L., L. siceraria , and S. purpurea fruits, respectively. In these studies, the antioxidant capacity of the hydrophilic and lipophilic phases was not determined separately.…”
Section: Resultssupporting
confidence: 92%
“…The antioxidant activity in Mexican plum fruit was always higher in the epicarp than in the pulp. Similarly, Ahmed et al [42] reported a higher antioxidant activity in the epicarp than in the pulp of Lagenaria siceria fruits and they explained that the abundance of phenols in the epicarp was the reason of this difference. The ecotype with the highest content of antioxidant activity present on either epicarp or pulp was 'Conservera de Tlaxmalac' with 5.1 mM antioxidant capacity equivalent to concentration of ascorbic acid (ACECA) g −1 FW in the rind and 1.6 mM ACECA g −1 FW in the pulp.…”
Section: Antioxidant Activitymentioning
confidence: 88%
“…TPC was estimated using Folin-Ciocalteu reagent (FCR) with gallic acid as the standard [18] . FCR being sensitive to reducing compounds including polyphenols produce blue colour upon reaction.…”
Section: Quantitative Estimation Of Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…The concentration of extract at which 50% inhibition is observed (IC 50 ) is calculated in µg/ml. Phosphomolybdate assay [18] :…”
Section: Quantitative Estimation Of Total Flavonoid Content (Tfc)mentioning
confidence: 99%